Expectations of first year undergraduate medical students towards human cadaveric dissection: reflective writing as an effective tool - Shah, S; Koirala, S; Khanal, VK; Yadav, GK; Khanal, L (Devdaha Medical Journal, 2025)
Introduction: Cadaveric dissection promotes psychosocial development and emotional socialization. The objective of this study was to assess the expectations of first year undergraduate medical students of BPKIHS towards human cadaveric dissection using a reflective writing exercise. Methods: Qualitative cross-sectional study was conducted before dissection Lab Exercise in Unit 0. Students were divided in twenty groups. Each group consist of 5 students and group leaders were also nominated for timely submission of questionnaire. Each group was instructed to meet their teams in person to discuss their questions before first dissection in department and write their responses to the reflective questions together in 200 words. After data collection, all the data were managed by research team. Qualitative analysis of reflective writing was done by grounded theory data analysis procedure. Afterwards, we framed levels of coding more specifically open, axial and selective coding. Results: The mean age of participants was 19.63 year; 74.5% were of Indo-Nepalese ethnic groups; 70.4% were male and 72.4% had seen dead body before admission to BPKIHS. Total 147 unique open codes were identified. These open codes were sorted into 8 axial codes such as gratitude/respect, story of patient, anatomy learning, humanity, career building, lifestyle/interpersonal modification, empathy and courage. Conclusion: The importance of cadaveric dissection in relation to education, career building, interpersonal and intrapersonal benefits were reported by our students.